2012
DOI: 10.2319/010112-1.1
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the effects of maxillary protraction using facemask and miniplate anchorage between unilateral and bilateral cleft lip and palate patients

Abstract: Objective: To determine the difference in the effects of facemask with miniplate (FM-MP) anchorage on maxillary protraction in growing cleft patients between unilateral (UCLP) and bilateral cleft lip and palate (BCLP) groups. Materials and Methods: The samples consisted of a UCLP group (N 5 15, 13 boys and 2 girls; mean age 10.98 years; mean protraction duration 2.37 years) and a BCLP group (N 5 15, all boys; mean age 11.42 years; mean protraction duration 2.36 years), who were treated with the same surgical t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
53
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(56 citation statements)
references
References 39 publications
2
53
0
1
Order By: Relevance
“…Numerous studies have shown that face mask has been applied to treat growing cleft lip and palate patients with mild-to-moderate maxillary hypoplasia. [3][4][5][6]14,15 Conventionally, a value of 5-N orthopedic force was applied in a direction that was 30 degrees downward and forward to the occlusal plane on the region of alveolar of maxillary canine. 8,16 Facial and skeletal balance improvement has been the main aim of contemporary orthodontics-dentofacial orthopedic treatment in patients with complete UCLP.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies have shown that face mask has been applied to treat growing cleft lip and palate patients with mild-to-moderate maxillary hypoplasia. [3][4][5][6]14,15 Conventionally, a value of 5-N orthopedic force was applied in a direction that was 30 degrees downward and forward to the occlusal plane on the region of alveolar of maxillary canine. 8,16 Facial and skeletal balance improvement has been the main aim of contemporary orthodontics-dentofacial orthopedic treatment in patients with complete UCLP.…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5][6] Recent studies revealed that the biomechanic effects of maxillary protraction on the craniofacial skeleton in cleft patients have not been well elucidated clinically and experimentally by using a finite element method (FEM), unlike those of noncleft patients. [7][8][9] The underlying mechanism of finite element analysis (FEA) on maxillary protraction for patients with UCLP is still unbeknown.…”
mentioning
confidence: 99%
“…Although the rotation pattern is beneficial for low-angle, deep-bite Class III patients, many studies 20,21 have demonstrated that facemasks were contraindicated in Class III patients with high angle facial type or openbite. In order to eliminate this counterclockwise rotation effect, various locations have been used for force application 7,22,23 : the canine region, premolar, and deciduous molar region. Nonetheless, those trials showed that the counterclockwise rotation of the maxilla was inevitable after facemask use.…”
Section: 16mentioning
confidence: 99%
“…2 Protraction facemask therapy is the most common approach for early treatment of these patients. 3 It has many drawbacks, including unwanted dentoalveolar effects and the excellent compliance needed with a troublesome extraoral appliance for satisfactory outcomes.…”
Section: Introductionmentioning
confidence: 99%